2021
DOI: 10.1111/andr.12998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of circulating testosterone concentration on sperm cryoresistance: The ibex as an experimental model

Abstract: Background: Recent studies have noted that the circulating testosterone concentration may affect the ability of spermatozoa to survive cryopreservation. However, few attempts to confirm such a relationship have been made. Wild ruminant species have very marked seasonal changes in their reproductive function and strong annual changes in their plasma testosterone concentration. Objectives:The present work examines the influence of induced changes in testosterone secretion on sperm variables following conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Coloma et al (2010) revealed that high levels of testosterone in the Iberian ibex blood plasma were associated with a decrease in progressive sperm motility and a decrease in acrosome and membrane integrity, and this relationship is characteristic only for the frozen-thawed sperm. Bóveda et al (2021) also found a reduction in the concentration of testosterone in the blood plasma of Iberian ibex and it increased with the sperm cryostability duration increases and vice versa. Moreover, these changes most likely occur at the final stage of sperm maturation in cauda epididymis and secretion of the sperm and may be associated with remodeling of the protein and lipid components of the sperm membrane.…”
Section: Resultsmentioning
confidence: 77%
“…Coloma et al (2010) revealed that high levels of testosterone in the Iberian ibex blood plasma were associated with a decrease in progressive sperm motility and a decrease in acrosome and membrane integrity, and this relationship is characteristic only for the frozen-thawed sperm. Bóveda et al (2021) also found a reduction in the concentration of testosterone in the blood plasma of Iberian ibex and it increased with the sperm cryostability duration increases and vice versa. Moreover, these changes most likely occur at the final stage of sperm maturation in cauda epididymis and secretion of the sperm and may be associated with remodeling of the protein and lipid components of the sperm membrane.…”
Section: Resultsmentioning
confidence: 77%
“…The influence of photoperiod/melatonin on AQP expression might be indirectly exerted via changes in the testosterone concentration, which in turn might be associated with reduced sperm cryoresistance. Indeed, it is known that high testosterone levels negatively affect sperm cryoresistance in both the examined species [ 30 ]. The present findings suggested that the negative influence of testosterone on sperm freezability may be mediated via AQP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite androgens have an important role in the activity of seminal vesicles and bulbourethral glands, their size was not modified after immunization against GnRH. It has been shown that even shortterm treatments with antiandrogens-that is, cyproterone, acetatereduce the area of seminal vesicles in wild goats (Bóveda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%